Association between the Use of Touchscreen Device and Child Development - Husada Tsalitsa Mardiansyah; Mira Irmawati; Dwi Susanti (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Early childhood development is related to sensitive period, a spesific period when a child is more easily stimulated by certain environmental stimulation. The right stimulation is needed to achieve good development. The intense use of touchscreen device is thought to potentially be a new form of stimulation that could affect child development. The aim of this study was to determine whether there is an association between the use of touchscreen device and child development. Methods: The design of this study was observational analytic with cross-sectional approach. The sampling technique used in this study was cluster-sampling. Data collection was finished in October 2018 by interviewing the respondents and assessing child development using development pre-screening questionnaire (KPSP). Results: Among 91 samples of this study, the majority (78.0%) had actively operated touchscreen devices by themselves. The result of the Kruskal Wallis test gave a value of p = 0.398 (p > 0.05) with the mean rank of not at all 29.50; only watching 48,53; and operating 46.09. Conclusion: The use of touchscreen device is not significantly associated with children development. Further research needs to be conducted to uncover the effect of touchscreen device on child development.